1965
DOI: 10.1126/science.147.3664.1448
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Released from the Cerebral Cortex in Relation to Its State of Activation

Abstract: The rate of release of gamma-aminobutyric acid from the perforated pial surface of the cerebral cortex in the cat showed systematic variations with the state of activation or "arousal" of the electrocorticogram. In animals subjected to midbrain coagulation and showing constant spindle patterns characteristic of sleep, the rate of release was three times greater (about 2 micrograms per hour per square centimeter) than in animals showing a largely "aroused" electrocorticogram, which had sections of the upper cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…For example. Mitchell and co-workers (Mitchell & Srinivasan, 1969;Iversen, Mitchell & Srinivasan, 1971), in an elegant series of experiments, demonstrated a Ca2+-dependent release of endogenous GABA following electrical stimulation of the cortical surface and of the lateral geniculate nucleus and an increase in GABA release following brain stem transaction has also been described (Jasper, Khan & Elliott, 1965;Jasper & Koyama, 1969). Apart from work in this laboratory (Clark & Collins, 1975;Collins 1975) there have been no reports of stimulation achieving a significant R. M. CLARK AND G. G. S COLLINS release of endogenous taurine although Jasper & Koyama (1969) reported an increase in release accompanying electrical stimulation of the mid brain reticular formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example. Mitchell and co-workers (Mitchell & Srinivasan, 1969;Iversen, Mitchell & Srinivasan, 1971), in an elegant series of experiments, demonstrated a Ca2+-dependent release of endogenous GABA following electrical stimulation of the cortical surface and of the lateral geniculate nucleus and an increase in GABA release following brain stem transaction has also been described (Jasper, Khan & Elliott, 1965;Jasper & Koyama, 1969). Apart from work in this laboratory (Clark & Collins, 1975;Collins 1975) there have been no reports of stimulation achieving a significant R. M. CLARK AND G. G. S COLLINS release of endogenous taurine although Jasper & Koyama (1969) reported an increase in release accompanying electrical stimulation of the mid brain reticular formation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that have examined effects of sleep on glutamate, most concentrate on the effects of sleep and sleep loss in the cortex. These studies have observed that glutamate in the cortex levels fluctuate progressively through sleep/wake states (Jasper et al 1965;Lopez-Rodriguez et al 2007). Few have examined the effects of sleep deprivation on cortical glutamate levels.…”
Section: Glutamatementioning
confidence: 99%
“…In 1965, it was first reported [33] that glutamate is released from the cortex of cats with the surface superfusion approach. It is also found that the release of glutamate was accompanied by the release of aspartate, glycine, and taurine after electrical stimulation.…”
Section: Glutamate In the Central Nervous Systemmentioning
confidence: 99%